Cointergration analysis of carbon dioxide emissions per capita and real GDP per capita and environmental kuznet curve hypothesis testing using data from five developing Asian countries. - Catedrilla, Aljon Rey P.; Lianos, Madeline A. (2015.)
The aim of this paper is to test the Environmental Kuznets Curve and the cointegration of carbon dioxide emissions per capita and real GDP per capita using time series data of five developing Asian countries form 1970 to 2010. Graphical method, Cointegrating Regression Dickey-Fuller (CRDF) test, Cointegrating Regression Durbin- Watson (CRDW) test and the Environmental Kuznets Curve (EKC) theory were used in this study. The results of CRDF show that the data from Indonesia, and Nepal are only cointegrated while the data in the Philippines and India do not exhibit conintegration. Cintegration of the data in Sri Lanka is not possible since it is not an I (I) process. While the results from CRDW show that data from India, indonesia, Philippines and Sri Lanka exhibit conintegration. The result of the study suggests that the EKC theory is evident among variables in five developing Asian countries.
Research Project (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines Visayas.
Keywords: Environmental Kuznets Curve theory